2015
DOI: 10.4158/ep15623.or
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D-Binding Protein in Healthy Pre- and Postmenopausal Women: Relationship with Estradiol Concentrations

Abstract: Objective To examine the relationship between endogenous serum estradiol and vitamin D–binding protein (DBP) and total, free, and bioavailable 25-hydroxyvitamin D (25OHD) concentrations in pre- and postmenopausal women. Methods In 165 healthy women (ages, 26 to 75 years) not taking any form of exogenous estrogen, the serum concentrations of estradiol, 25OHD, DBP, parathyroid hormone, and albumin were measured. Free and bioavailable 25OHD (free + albumin-bound) levels were calculated from total 25OHD, DBP, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 36 publications
2
30
0
Order By: Relevance
“…A prior study found that pre-menopausal women had higher levels of total 25(OH)D, vitamin D binding protein, and calculated free and bioavailable 25(OH)D compared to postmenopausal women, and that serum E2 levels correlated with vitamin D binding protein. [32] Thus, associations between vitamin D and E2 might be more clinically meaningful in pre-menopausal women, but we were unable to test for that in our cohort.…”
Section: Discussionmentioning
confidence: 90%
“…A prior study found that pre-menopausal women had higher levels of total 25(OH)D, vitamin D binding protein, and calculated free and bioavailable 25(OH)D compared to postmenopausal women, and that serum E2 levels correlated with vitamin D binding protein. [32] Thus, associations between vitamin D and E2 might be more clinically meaningful in pre-menopausal women, but we were unable to test for that in our cohort.…”
Section: Discussionmentioning
confidence: 90%
“…Fourth, there were statistically significant differences in age, gender, and albumin levels among our groups (Table 1). Because young age and female sex are associated with high VDBP levels [2324] and the bioavailable 25(OH)D calculation includes the albumin level, our results on the differences in VDBP levels and in the calculated bioavailable 25(OH)D levels among the groups could be affected by these differences in characteristics of the study subjects. Nonetheless, the calculated bioavailable 25(OH)D may reflect the status of VDBP levels and the albumin levels in each patient; therefore, calculated bioavailable 25(OH)D could be used to assess vitamin D status accurately in the patients with altered VDBP levels or albumin levels.…”
Section: Discussionmentioning
confidence: 99%
“…We conducted a comprehensive literature review in the Medline database for these six proteins, to investigate their relevance regarding bone metabolism and their potential use as biomarkers. The proteins GSN, CP, and VDBP have previously been related to bone metabolism and proposed as potential biomarkers to identify BMD variation [21][22][23][24][25][26][27]. Additionally, we included other proteins with a role in bone remodeling or metabolism, as described in previous studies, such as alpha-2-S-glycoprotein (AHSG) [28,29], alpha-1-antitrypsin (SERPINA1) [30], and haptoglobin (HP) [31].…”
Section: Maldi-tof/tof Protein Identification Analysismentioning
confidence: 99%